CALORIMETRIC MEASUREMENTS OF FUSION ENTHALPIES FOR NI2SIO4 AND CO2SIO4 OLIVINES AND APPLICATION TO OLIVINE-LIQUID PARTITIONING - Sugawara T.; Akaogi M. (My University, 2003)
Calorimetric measurements of fusion enthalpies for Ni2SiO4 and Co2SiO4 olivines were carried out using a high-temperature calorimeter, and Ni and Co partitioning between olivine and silicate liquid was analyzed using the measured heats of fusion. The fusion enthalpy of Co2SiO4 olivine measured by transposed-temperature drop calorimetry was 103 +/- 15 kJ/mol at melting point (1688 K). The fusion enthalpy of Ni2SiO4 olivine was calculated based on the enthalpies of liquids in the system An50Di50-Ni2SiO4 measured by transposed-temperature drop calorimetry at 1773 K, and was 221 +/- 26 kJ/mol at its metastable melting point (1923 K). The fusion enthalpy of Ni2SiO4 is the largest among those of olivine group, this is caused by the large crystal field stabilization energy of six-coordinated Ni2+ in olivine. The larger fusion enthalpy of Ni2SiO4 can account for the large and variable partition coefficient of Ni between olivine and silicate liquid. Based on the comparison between partition coefficients calculated from thermodynamic data and those observed in partition experiments, it is considered that the magnitude of partition coefficients is primarily dependent on the heats of fusion of the components. Furthermore, the activity coefficients for Ni-, Co- and Mn-bearing components in magmatic liquid are nearly of the same magnitude.